1989
DOI: 10.1136/jnnp.52.8.1010
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis and dual primary infection with human immunodeficiency virus and cytomegalovirus.

Abstract: Cerebral venous thrombosis and dual primary infection with human immunodeficiency virus and cytomegalovirus Sir: Cerebral venous thrombosis (CVT) is rarely associated with well-documented viral infections'2 and has not been described in association with human immunodeficiency virus type 1 (HIV,) or cytomegalovirus (CMV) infection, to our knowledge. We report a case of CVT occurring during primary infection with both HIV, and CMV;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…There are many reports of thrombosis occurring in patients with HIV/AIDS and these include peripheral vein (Becker et al, 1992;Tanimowo, 1996), pulmonary embolism (Becker et al, 1992), retinal vein (Roberts and Haefs, 1992;Mansour et al, 1996;Park et al, 1997;Friedman and Margo, 1995), cerebral vein (Meyohas et al, 1998), portal vein (Carr et al, 1997) and mesenteric (Narayanan et al, 1998;Wang et al, 2000) occlusions. Both arterial and venous thromboembolic disease has been reported in one patient (Bosson et al, 1995).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 95%
See 2 more Smart Citations
“…There are many reports of thrombosis occurring in patients with HIV/AIDS and these include peripheral vein (Becker et al, 1992;Tanimowo, 1996), pulmonary embolism (Becker et al, 1992), retinal vein (Roberts and Haefs, 1992;Mansour et al, 1996;Park et al, 1997;Friedman and Margo, 1995), cerebral vein (Meyohas et al, 1998), portal vein (Carr et al, 1997) and mesenteric (Narayanan et al, 1998;Wang et al, 2000) occlusions. Both arterial and venous thromboembolic disease has been reported in one patient (Bosson et al, 1995).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 95%
“…Certainly, thrombotic and other manifestations are much more frequently encountered than with other viral infections, again pointing to a major immunological disturbance in HIV as opposed to other viral conditions. However, dual infection with HIV and CMV has been reported as being associated with APS in a number of patients (Meyohas et al, 1998;Smith et al, 1995;Bagley et al, 1986;Jenkins et al, 1991).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 97%
See 1 more Smart Citation
“…Another report found that IgG and IgM isotypes of aCL were detected in CMV infections, with a high prevalence (56%) of aPL being reported in patients with CMV infection, although no association was found between these antibodies and the clinical expression of autoimmunity [36]. Meyohas et al reported [43] that dual viral infection with CMV and HIV resulted in thrombotic manifestations of APS, including digital infarcts [41][42][43].…”
Section: Other Viral Infections and Antiphospholipid Antibodiesmentioning
confidence: 95%
“…49 Other frequently seen causes include Factor V Leiden, 1 protein C, 28 or protein S 39 deficiencies; antiphospholipid syndrome; 45 vasculitis; 26 or infections. 38 It has been suggested that pseudotumor cerebri is due to undiagnosed CVT, and one study has suggested that MR venography should be done unless MR imaging is diagnostic for CVT in any patient with presumed IIH, to rule out this condition. Lin et al 34 found that 9.4% of patients (10 of 106) meeting criteria for IIH had thrombosis evident on MR venography.…”
mentioning
confidence: 99%